Careless in red - George, Elizabeth (New York : Harper, 2009)
Scotland Yard's Thomas Lynley discovers the body of a young man who appears to have fallen to his death. The closest town, better known for its tourists and its surfing than its intrigue, seems an unlikely place for murder. However, it soon becomes apparent that a clever killer is indeed at work, and this time Lynley is not a detective but a witness and possibly a suspect.
Keywords: Police -- England -- Fiction; Bereavement -- Psychological aspects -- Fiction; Detective and mystery fiction